LEXICAL METAPHOR IN INDONESIAN VERSION OF SURAH AL-KAHFI - Mirwana . Siska; Zainuddin . .; Anni Holila Pulungan (Universitas Negeri Medan, 2021)
ABSTRACTIn communication, people often faced to the use of metaphor, but many of us sometimes don't understand the metaphor itself. People usually find metaphors when using language in communication where the language they want to say is different from the actual meaning. metaphor divided into two; lexical metaphor and grammatical metaphor and lexical metaphor. This research focus on lexical metaphor that shows variations of words in which there are veiled meanings or different meanings. This research aims to explain why lexical metaphors are used in the Surah Al-Kahfi. This research revealed that (+) specialized, un-equal, formal and written have some frequency. All of them were found 42 times or 100%. Meanwhile, the (-) specialized, equal, informal and spoken with zero experience. the researcher was interested to conduct a research about lexical metaphor that used in Surah Al-Kahfi with Bahasa Indonesia translation version of the Qur’an. Keywords: Metaphor, Lexical Metaphor, Al-Qur’an, Surah Al-Kahfi